Mapping sewage treatment plants for wastewater reclamation and reuse in industrial parks of Peninsular Malaysia: A path towards water security - Nur Hairunnisa Rafaai; Khai Ern Lee; Noor Zarina Mohd Nazir; Ainul Rasyidah Ab Rahim; Thian Lai Goh; Mazlin Mokhtar; Wan Abd Rahim Wan Abdullah; Huzaini Husain; Raja Baharudin Raja Mamat (Water Resources and Industry)
The rapid industrialisation and urbanisation in recent decades have significantly increased global wastewater generation, particularly in industrial parks. Sewage treatment plants (STPs) near these parks are crucial for promoting sustainable practices. Instead of discharging treated wastewater, reclaiming and reusing it can minimise the water footprint. However, there has been insufficient evaluation of wastewater reclamation potential within existing STPs. This study integrates the Analytical Hierarchy Process (AHP) with spatial analysis to assess the suitability of STPs for wastewater reclamation and reuse in Peninsular Malaysia's industrial parks. Factors considered include STP design capacity, wastewater quality, proximity to industries, non-domestic water tariffs and geographical features. AHP analysis assigned weights to these factors, achieving a consistency ratio of less than 0.10. The resulting suitability map categorises STPs into five levels, showing that 64 % of the land area and 40.5 % or 2922 of STPs have very low reclamation potential due to inadequate wastewater management infrastructure. In contrast, only 0.1 % of the land and 0.2 % or 17 of STPs out of approximately 7208 STPs exhibit high reclamation potential. A holistic approach is essential to evaluate multiple factors, enabling operators to identify suitable STPs for reclamation and ensuring regional water security.